2016
DOI: 10.3233/jad-151093
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Fitness in the Neurocognitive Performance of Task Switching in Older Persons with Mild Cognitive Impairment

Abstract: Abstract. Although elderly people with amnestic mild cognitive impairment (aMCI) have been found to show impaired behavioral performance in task switching, no research has yet explored the electrophysiological mechanisms and the potential correlation between physical fitness and neurocognitive (i.e., behavioral and electrophysiological) performance in aMCI. The present study was thus aimed to examine whether there are differences in electrophysiological (i.e., event-related potential) performance between aMCI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 90 publications
(157 reference statements)
1
19
0
Order By: Relevance
“…Previous studies have proposed that the ERP P3 component is sensitive enough to identify an early stage of cognitive impairment in the elderly with MCI ( Bennys et al, 2007 , Jiang et al, 2015 , Tsai et al, 2016a ). Even though Wang et al, 2013 found that older adults with MCI showed longer P3 latencies than healthy controls when performing the Flanker task, and Kamijo et al, 2009 found that the P3 latency following a bout of light or moderate aerobic exercise was shorter than during the baseline session in older adults when performing the Flanker task, acute bouts of exercise, regardless of aerobic or resistance mode, failed to modulate the P3 latency in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have proposed that the ERP P3 component is sensitive enough to identify an early stage of cognitive impairment in the elderly with MCI ( Bennys et al, 2007 , Jiang et al, 2015 , Tsai et al, 2016a ). Even though Wang et al, 2013 found that older adults with MCI showed longer P3 latencies than healthy controls when performing the Flanker task, and Kamijo et al, 2009 found that the P3 latency following a bout of light or moderate aerobic exercise was shorter than during the baseline session in older adults when performing the Flanker task, acute bouts of exercise, regardless of aerobic or resistance mode, failed to modulate the P3 latency in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…After baseline measurements as mentioned below, they were randomly assigned to either an aerobic exercise (AE, n = 25), a resistance exercise (RE, n = 21) or a control group (n = 20). The clinical inclusion criteria for the participants with aMCI were as follows while stratifying for age and gender ( Petersen, 2004 , Petersen et al, 1999 , Suk et al, 2014 , Tsai et al, 2016a ): (1) subjective memory complaints confirmed by family members; (2) objective memory impairment for age; (3) a Clinical Dementia Rating (CDR) of 0.5; (4) Mini-Mental State Examination (MMSE) score > 24 ( Folstein et al, 1975 ); (5) absence of significant levels of impairment in other cognitive domains (e.g., attention, language, orientation, and abstraction), as assessed by the Cognitive Abilities Screening Instrument (CASI) ( Teng et al, 1994 ); (6) largely intact functional activities of daily living; (7) no brain abnormalities (e.g., stroke and malignant brain tumors) seen via structural MRI scans; (8) an absence of dementia; and (9) non-depressed, with a score of < 13 on the Beck Depression Inventory, 2nd edition (BDI-II) ( Beck et al, 1996 ). Single photon emission computed tomography (SPECT) for functional examinations and computed tomography (CT) for structural brain examinations were performed when more information was needed to confirm the diagnosis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen of the 29 total studies assessing P300 amplitude in MCI reported no significant difference between groups [i.e., 55%;11,22,28-30,46,51,78,94,105- 107,114,133,139,142]. Of the remaining 13 studies that reported group differences (i.e., 45%), 11 reported smaller P300 amplitudes in MCI compared to HC groups [i.e., 85% of significant studies; 38% of total studies;12,23,53,57,59,81,83,86,138,145,148], including one that specified smaller amplitudes in progressive MCI compared to both non-progressive MCI and healthy controls[12]. Of the studies that detected group differences, 73% used more complexRunning head: SYSTEMATIC REVIEW OF COGNITIVE ERPS IN MCI AND AD 20…”
mentioning
confidence: 99%